Substrate heating method for coating metal surfaces with high-silica zeolites: ZSM-5 coatings on stainless steel plates - Tatlier, Melkon; Demir, Mesut; Tokay, Begüm; Erdem-Şenatalar, Ayşe; Kiwi-Minsker, Lioubov; Ungun, Ayşe Erdem (Elsevier BV, 2007)
Syntheses of ZSM-5 coatings on stainless steel plates were carried out via the substrate heating method. The reaction mixture was kept at temperatures below 100 °C, while the metal plates were heated to temperatures above 100 °C. It was demonstrated that continuous ZSM-5 coatings of different textures with different crystal morphologies and void fractions could be formed. ZSM-5 coatings were characterized by X-ray diffraction and scanning electron microscopy. The thickness of the ZSM-5 coatings could be varied depending on the synthesis conditions. Besides providing the opportunity of manipulating coating properties, the method is also beneficial in respect to the synthesis duration as compared to the conventional procedures.